Investigation of the relationship among fatigue, self-efficacy and quality of life during chemotherapy in patients with breast, lung or gastrointestinal cancer - Akin, Semiha; Kas Guner, Canan (Wiley, 2018)
To explore the relationship between fatigue and self-efficacy, and quality of life (QoL) during chemotherapy of patients with breast, lung or gastrointestinal cancers. This study is a descriptive-correlational research. The study population comprised of patients with breast, lung and gastrointestinal cancer treated at the outpatient chemotherapy unit. Patients' self-efficacy and QoL were assessed using Functional Assessment of Chronic Illness Therapy-Fatigue scale and Strategies Used by Patients to Promote Health scale. The sample included 236 patients receiving chemotherapy for lung cancer (30.9%), gastrointestinal (25.8%) or breast cancers (25.4%). The patients had little confidence in performing self-care self-efficacy during chemotherapy for the management of illness and chemotherapy-related side effects. The study found that the patients with cancer were moderately fatigued and all the domains of QoL of patients with cancer undergoing chemotherapy were considerably impaired. Positive correlations were found between self-efficacy scores and fatigue scores (p < 0.001), and QoL scores (p < 0.001). Better self-efficacy beliefs were associated with better QoL and lower fatigue. Improving the cancer patients' self-confidence in performing self-care behaviours may have a positive impact on performing cognitive and behavioural fatigue management strategies and can influence positively the patients' QoL during chemotherapy.
Keywords: Adult; Aged, 80 and over; Male; Lung Neoplasms; Organoplatinum Compounds; Paclitaxel; Leucovorin; Antineoplastic Agents; Breast Neoplasms; Middle Aged; Self Care; Antineoplastic Combined Chemotherapy Protocols; Quality of Life; Humans; Female; Fluorouracil; Colorectal Neoplasms; Fatigue; Aged; Gastrointestinal Neoplasms; 3. Good health